EVALUASI PRAKTIK PENGALAMAN LAPANGAN MAHASISWA UNIVERSITAS SUNAN GIRI SURABAYA TERHADAP AL-QUR’AN SEBAGAI SUMBER ILMU ISLAM - Amiril Wahid , Achmad; Yusron Maulana El-Yunusi, Muhammad (Program Studi Pendidikan Agama Islam STIT al Urwatul Wutsqo Bulurejo Jombang, 2024)
The Field Experience Practice Program (PPL) is a mandatory program carried out by postgraduate students of the Islamic Religious Education (PAI) study program who receive LPPD scholarships from the East Java provincial government. The PPL program is part of the courses that have been programmed in semester III (three) which are held on the Sunan Giri University Surabaya campus. The theme presented in the PPL is about the Al-Qur'an as a source of Islamic knowledge. This research is a qualitative research to describe the Al-Qur'an which is the holy book of Muslims as the mother of all knowledge. The data sources in this research were PAI postgraduate scholarship students, tutor lecturers, and an audience of undergraduate students. The data in this research are the results of interviews and documentation of the program. The research results show that the PPL program at Sunan Giri University Surabaya in 2023/2024 was carried out for one day. Postgraduate students who want to carry out the PPL program receive directions in the form of material that will be presented to the audience, then they present the theme using a public lecture model according to the predetermined schedule. The findings in this research show that the PPL program provides many benefits for practical students. The theories they learn in college can be implemented well in this PPL. Apart from that, they also gain experience in administration and management which other students do not get.